2013
DOI: 10.3400/avd.oa.13-00062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Characteristics and Detectability of Skin Perfusion Pressure Measured Using a Thermostatic Heating Probe

Abstract: Objectives: To assess the characteristics of skin perfusion pressure (SPP) measured using a thermostatic heating probe and whether a thermostatic heating probe improves SPP detection. Methods:We studied 8 feet of healthy young subjects and 31 feet of elderly patients suspected to have severe limb ischemia. We measured SPP at the dorsum and plantar aspects of each foot using a plain laser Doppler probe and a thermostatic heating probe heated at 44°C. Results were expressed as median. Comparisons were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition to its use in the diagnosis of critical limb ischemia (CLI) (20), in evaluating the severity of ischemia (21)(22)(23)(24), in the selection of the amputation plane (25), and in predicting wound healing, SPP is also used to evaluate the therapeutic efficacy of arterial revascularization surgery (26,27), endovascular therapy (28), and medicines used for the treatment of peripheral artery disease (PAD) and CLI (29,30). In a previous study, Watanabe et al (31) revised the laser Doppler technology, and SPP was measured using a thermostatic heating probe. It was demonstrated that this was useful for improving the detectability of SPP in ischemic limbs, and that an increase in SPP following heating may be a potential predictor of limb ischemia.…”
Section: Measurement Of Sppmentioning
confidence: 99%
“…In addition to its use in the diagnosis of critical limb ischemia (CLI) (20), in evaluating the severity of ischemia (21)(22)(23)(24), in the selection of the amputation plane (25), and in predicting wound healing, SPP is also used to evaluate the therapeutic efficacy of arterial revascularization surgery (26,27), endovascular therapy (28), and medicines used for the treatment of peripheral artery disease (PAD) and CLI (29,30). In a previous study, Watanabe et al (31) revised the laser Doppler technology, and SPP was measured using a thermostatic heating probe. It was demonstrated that this was useful for improving the detectability of SPP in ischemic limbs, and that an increase in SPP following heating may be a potential predictor of limb ischemia.…”
Section: Measurement Of Sppmentioning
confidence: 99%